Supernovæ: Workshop 8. Issue Volume 14:Issue S339(2018) (November 2017) - Stritzinger, M.; Moriya, T. J.
Abstract: This Workshop covered a cornucopia of topics that were featured in short formal presentations, followed by a round-table discussion. G. Hosseinzadeh and H. Kuncarayakti presented the results of their recent researches into interacting supernovæ. They included both the intriguing Type Ibn supernova subclass, and SN 2017dio, which appears to be the first Type Ic supernova to be seen to exhibit signatures of hydrogen-rich circumstellar interaction at all phases. M. Sullivan provided a summary relating to the future of transient science in the era of Big Data, and participants discussed strategies to determine which targets and fields should be selected for spectroscopic follow-up. The Workshop concluded with a rather heated discussion regarding the need for the IAU Supernovæ Working Group to consider modifying the current criterion for a confirmed supernova in order for it to receive an official IAU designation.